Resilience in the European Neighborhood Policy - N. N. Gudalov; E. Yu. Treshchenkov (Контуры глобальных трансформаций: политика, экономика, право, 2020)
This paper explores the articulation of the resilience concept in the policies of the European Union to the Eastern and Southern neighborhoods. In the discourse of foreign policy and security of the EU Global Strategy 2016, this concept appears as a key one. The idea is to empower the neighboring countries in their autonomous  efforts to build such resilience that would allow them to absorb a wide range of security threats without projecting them on the European Union. An analysis of the place of resilience in the evolution of the  European Neighborhood Policy, as well as in relations with neighbors to the East and South, allows us to draw conclusions regarding the novelty of the approach, as well as the prospects and obstacles to its implementation. The EU policy is analyzed along key dimensions for the concept of resilience: systems, threats, and resources.  At its core, the EU’s approaches have changed little, which can come into conflict with the cornerstone ideas of resilience thinking. For example, there is a tendency to assess the social and cultural practices existing in theneighboring countries through the prism of “right” and “wrong”, thus excluding them from resources of building resilience. In the case of the Eastern Neighborhood, Brussels did not refuse to promote here a full package of reforms aimed at spreading European practices to the states of the region. This is based on the perception of the region as a part of Wider Europe. The problems of the Southern Mediterranean and the Middle East, on the contrary, are increasingly merging in the eyes of the EU with those of the entire African continent. In the discourse and the policy of the European Union, disregard of the region’s problems may impede the formation of higher-quality forms of resilience in the South.